2012
DOI: 10.1002/ece3.383
|View full text |Cite
|
Sign up to set email alerts
|

Rainfall seasonality and pest pressure as determinants of tropical tree species' distributions

Abstract: Drought and pests are primary abiotic and biotic factors proposed as selective filters acting on species distributions along rainfall gradients in tropical forests and may contribute importantly to species distributional limits, performance, and diversity gradients. Recent research demonstrates linkages between species distributions along rainfall gradients and physiological drought tolerance; corresponding experimental examinations of the contribution of pest pressure to distributional limits and potential in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
59
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(67 citation statements)
references
References 46 publications
6
59
2
Order By: Relevance
“…We also found little evidence for species having lower mortality rates “at home” (Table ) and we found no evidence for a “home advantage” (Table ). These results indicate that the role of first‐year mortality responses to SWP in shaping species distributions was relatively minor, even though experiments suggest that first‐year mortality influences distributions with respect to variation in water, nutrient, and light availability (Baltzer & Davies, ; Engelbrecht & Kursar, ; Engelbrecht, Kursar, & Tyree, ; Lucas, Bruna, & Nascimento, ). Contrasting with our results, larger seedlings (20–50 cm tall) of dry‐associated species had lower mortality than wet‐associated species in the same 50‐ha plot, particularly on the dry plateau (i.e., “home advantage”) in a severe dry season (Comita & Engelbrecht, ).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…We also found little evidence for species having lower mortality rates “at home” (Table ) and we found no evidence for a “home advantage” (Table ). These results indicate that the role of first‐year mortality responses to SWP in shaping species distributions was relatively minor, even though experiments suggest that first‐year mortality influences distributions with respect to variation in water, nutrient, and light availability (Baltzer & Davies, ; Engelbrecht & Kursar, ; Engelbrecht, Kursar, & Tyree, ; Lucas, Bruna, & Nascimento, ). Contrasting with our results, larger seedlings (20–50 cm tall) of dry‐associated species had lower mortality than wet‐associated species in the same 50‐ha plot, particularly on the dry plateau (i.e., “home advantage”) in a severe dry season (Comita & Engelbrecht, ).…”
Section: Discussionmentioning
confidence: 96%
“…As we found that mortality rates declined rapidly with seedling height for all species (Green, Harms, & Connell, ; Rose & Poorter, ), a growth advantage allows seedlings to escape the vulnerable small seedling stage more rapidly (Kitajima & Fenner, ) than seedlings of other species. Experiments have documented species‐specific responses of seedling growth to water availability (Ashton et al, ; Baltzer & Davies, ; Born et al, ; Bunker & Carson, ; O'Brien, Ong, & Reynolds, ; O'Brien, Philipson, Tay, & Hector, ; Yavitt & Wright, ). Our study is the first to show that differential growth responses of naturally regenerating seedlings contribute to local species distributions along a gradient of soil water availability.…”
Section: Discussionmentioning
confidence: 99%
“…Enhanced density‐ and distance‐dependent insect herbivory in less seasonal and more humid forests has been suggested to contribute to this pattern (Janzen , Connell , Coley & Barone , Leigh et al . , Baltzer & Davies ).…”
mentioning
confidence: 96%
“…Whilst drought‐tolerant species tend to have a higher capacity for water conductance and CO 2 assimilation under water‐limiting conditions, they grow more slowly in the scarce understory light of wet forests where shade‐tolerant species have a competitive advantage (Brenes‐Arguedas et al , , Gaviria and Engelbrecht ). Drought‐tolerant species are also apparently more vulnerable to pest damage in moist areas (Baltzer and Davies , Spear et al ). Thus, in less physiologically stressful environments, tropical tree species' occurrences could be limited by stronger biotic interactions, both with competitors and natural enemies (MacArthur , Normand et al ).…”
mentioning
confidence: 99%